ABCB1 polymorphism predicts the toxicity and clinical outcome of lung cancer patients with taxane‐based chemotherapy. Issue 11 (30th September 2019) - Zhong, Jia; Guo, Zihan; Fan, Liping; Zhao, Xinghui; Zhao, Bingqing; Cao, Zhigang; Cheng, Linlin; Shi, Yuanyuan; Li, Xiaoting; Zhang, Yanhua; An, Tongtong; Wu, Meina; et al.
Abstract : Background: Taxane‐based chemotherapy is widely used in lung cancer. ABCB1 have a role in the prediction of treatment response and toxicity of chemotherapy in solid tumors. In this retrospective study, we investigated ABCB1 polymorphism on response and toxicity in taxane‐based chemotherapy in lung cancer patients. Methods: A total of 122 lung cancer patients who received taxane‐based chemotherapy were included in this study. Fluorescence in situ hybridization (FISH) was used for ABCB1 polymorphism detection. Turbidimetric inhibition immunoassay was used for pharmacokinetic analysis. Statistical analysis was performed using SPSS 20.0. Results: The frequency of the ABCB1 2677 site TT/TG/GG genotype was 32.8%, 43.4% and 23.8%, respectively and the frequency of the 3435 sites the TT/TC/CC genotype was 13.9%, 44.3% and 41.8%, respectively. The occurrence of neurotoxicity was higher in patients who had ABCB1 3435 site mutation (TT 88.2%, TC 22.2%, CC 21.6% P = 0.004). There was no significant difference between ABCB1 genotypes with regard to other chemotherapy‐induced toxicity. For non‐small cell lung cancer (NSCLC) patients, those harboring ABCB1 2677 and 3435 site wild‐type patients had longer median progression‐free survival (PFS) in the paclitaxel subgroup (3435 site: TT 3.87 vs. TC 9.50 vs. CC 14.13 months; P < 0.001; 2677 site: TT 4.37 vs. TG 9.73 vs. GG 12.1 months; P = 0.013). The area under the concentration‐time curve (AUC) of 20 patients treated with docetaxel increased for ABCB1 mutation subgroups. Conclusion: ABCB1 mutation is associated with higher neurotoxicity of taxane‐based chemotherapy. It also predicts shorter PFS for NSCLC in paclitaxel‐based treatment.